1989
DOI: 10.1055/s-2007-999586
|View full text |Cite
|
Sign up to set email alerts
|

Drug Ingestion During Pregnancy: Infrequent Exposure in a Contemporary United States Sample

Abstract: Drug ingestion in a cohort of United States women proved consistently lower than in prior United States populations. Participating were 342 insulin-dependent diabetic and 387 control subjects who were enrolled before conception (76%) or no later than 21 days after conception (24%). Drug exposures were then recorded at entry and periodically throughout organogenesis (gestational weeks 6, 8, 10). During gestational weeks 1 to 10, approximately two thirds of the subjects were exposed to no agent other than oral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…During the last few years of the study, the incidence of one malformation -ventricular septal defectnearly doubled at a time when progestin use was declining sharply. Consistent with the observations of Wiseman [4] is the finding of only 2 progestin exposures among 729 women followed by Simpson et al [3].…”
Section: Cardiac Anomaliessupporting
confidence: 89%
See 1 more Smart Citation
“…During the last few years of the study, the incidence of one malformation -ventricular septal defectnearly doubled at a time when progestin use was declining sharply. Consistent with the observations of Wiseman [4] is the finding of only 2 progestin exposures among 729 women followed by Simpson et al [3].…”
Section: Cardiac Anomaliessupporting
confidence: 89%
“…In 1978, Doering and Stewart [2] found 65% of their study population exposed to hormones. A trend toward decreased drug ingestion during pregnancy was delineated for a United States population by Simpson et al [3]. A cohort of 729 women was recruited prior to conception, insulin-dependent diabetics and non-diabetic controls.…”
Section: General Commentsmentioning
confidence: 99%
“…37 Additional analyses were undertaken with individual items grouped together by organ systems: skull, heart, skeleton, gastrointestinal, and genitourinary. Simple comparisons of continuous outcomes were made using Student's t test or the Wilcoxon rank sum test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…As the frequency of exposures is reduced, the recognition of teratogenesis may become impossible by epidemiologic approaches. 91 The epidemiologic investigation of drug teratogenesis presents numerous other difficulties, including multiple use of drugs, the dependence on maternal recall, inadequate concurrent documentation of drug use, and uncertainty regarding timing and dosage. Selected epidemiologic studies of the risk of overall cardiovascular malformations, shown on Table 8, illustrate the inconsistencies in the findings of two casecontrol studies, 92 ' 93 and data on the same agents from the Baltimore-Washington Infant Study.…”
Section: Therapeutic Use Of Drugsmentioning
confidence: 99%